Theory Of Reasoned Action: The Effect Of Halal Awareness And Family Support On Smes Halal Certification Behavior - Margarena, Agung Novianto; Aulia, Zakky Fahma; Prasetyawan, Arian Agung (Universitas Islam Negeri Sunan Kudus, 2024)
Analyzing the low number of halal certifications through the Theory of Reasoned Action framework. Moreover, Indonesia as the largest Muslim country has not yet entered the top 10 of the world's halal industry in several sectors. This research is classified as quantitative research with a sampling technique through snowball sampling with 144 respondents as SMEs owners in Salatiga City. This research uses SEM AMOS analysis tool. The results of the study indicate that halal awareness and family support have a significant effect both directly and indirectly through intentions on the behavior of SMEs halal certification. This study recommends strengthening halal awareness and family support through Halal Product Companion (PPH). The government must encourage the participation of Halal Product Companion (PPH) in the Ministry of Religion's Halal Product Assurance Agency (BPJPH) to encourage halal certification.